“DIDACTIC AND PSYCHOLOGICAL OPTIMIZATION OF VISUAL CONTENT USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES” - Qudratov Hasanali Otabek o‘g‘li (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the didactic and psychological optimization of visual content in education through Artificial Intelligence (AI) technologies. AI tools enable educators to design learning materials that are both pedagogically effective and psychologically engaging, enhancing comprehension, motivation, and retention among students. The study highlights the integration of AI for content adaptation, personalized learning paths, and real-time feedback, emphasizing its role in creating interactive and learner-centered educational experiences.